Некоторые закономерности развития хрящевой и костной тканей - Мажуга, П.М. (Вестник зоологии, 1967)
On the basis of the data of special literature and on the author's observations, the question of interrelation between the cartilage and bone tissues in philo- and ontogenesis is considered. The facts presented here do not allow to regard various conditions of skeletal tissues as stages of a single evolutionary process of cartilage and bone histogenesis. The various differentiations of cartilage and bone tissues originated and originate in the skeleton of vertebrates, apparently, as a result of concrete conditions of their development ano functioning.